Revision of the Miocene caviomorph rodents from the Río Santa Cruz (Argentinean Patagonia) - Arnal, Michelle (2019)
Fossil rodents from the Río Santa Cruz (RSC) classic localities (Santa Cruz Formation, Early–Middle Miocene) are known by the works of F. Ameghino and W.B. Scott since the end of the 19th and beginning of the 20th centuries. These caviomorph rodents have not been comprehensively reviewed since then. In this contribution, we studied new fossil specimens from the cliffs of the RSC (Province of Santa Cruz, Argentina) collected with accurate stratigraphic and geographic data during fieldtrips in 2013 and 2014. An increase in the caviomorph taxonomic richness is observed, based upon our taxonomic study of caviomorphs previously recorded in the RSC. Also, these fieldworks recovered for the first time several taxa previously found in other Santacrucian and even older Patagonian localities (Colhuehuapian, Early Miocene). As a general evolutionary pattern, we note an increase of derived euhypsodont taxa (Prolagostomus, Pliolagostomus, Schistomys, and Eocardia) in Segundas Barrancas Blancas (16.47–15.3 Ma). In addition, a taxonomic replacement of Phanomys by Schistomys is noted between Barrancas Blancas (17.21–16.3 Ma) and Segundas Barrancas Blancas, as well as a notably increase in the abundance of the large Perimys onustus in the latter locality. The present study provides a revision of the caviomorph systematics, and intends to be the starting point to understand the diversity (in all its aspects) and the evolution of this group during the Santacrucian, a major event in the South American mammalian history.